STOSOWANIE RZYMSKICH USTAW KARNYCH WOBEC PIRATÓW - Tarwacka, Anna (Zeszyty Prawnicze, 2017)
The Usage of the Roman Criminal Laws against Pirates Summary The last two centuries of the Roman Republic were a period of the most intensive piratical activity in the Mediterranean Sea. The Romans recognized this peril too late to be able to deal with it easily. Piracy of this period may be considered a crime on an international scale. There were no separate legal acts penalizing piracy, the maritime bandits were subject to the leges penalizing single crimes. Among these the most important were the leges de vi concerning using of force in public and private life; lex Cornelia de sicariis et veneficis penalizing murder and carrying of weapons. These regulations were further extended to punish theft from shipwrecks and violence against sailors. Selling free citizens and and taking them hostage was subject to the lex Fabia de plagio.